Fora da mídia e dentro do salão: samba-rock e mestiçagem - Rodrigues, Vagner (2006)
Through forty years of gradual interaction of certain elements between local and foreign cultures in the popular districts of São Paulo, the permanence of Samba-Rock, a hybrid dance form, has come in to being. Even though it has been marginalized by the written and broadcast media, Samba-Rock survives and keeps its power to contaminate. This research will offer some theses on this singular hybrid dance form, which has come about only through CD's LP's, family parties, balls and so on. In this investigation, an understanding of what happens to the body when dancing Samba-Rock is fundamental, and for this reason the Theory of Corpomidia, develeloped by Helena Katz and Christine Greiner serves as a guide to a bibliography which includes works dedicated to the political cultural studies by Homi Bhabha, Zygmunt Baumam and Nestor Garcia Canclini. To understand Samba-Rock in context it is necessary to reflect on present day culture in communion with the bibliographic works of neo evolutionists like Richard Dawkins and Daniel Dennett. The proposed relatioship between neo evolutionists and political culture studies will be seen through a methodology based on bibliographic revision and in situ investigation including interviews